DYNAMIC PLASMA-MODIFIED BENTONITE-BASED SORBENTS OF NEKRYLOVSKY SITE OF THE TARASOVSKY FIELD DEPOSIT - Aleksandra Igorevna, Grigor’eva; Larisa Stanislavovna, Grigor’eva; Mikhail Gerasimovich, Bruyako (Stroitel'stvo : Nauka i Obrazovanie, 2018)
Currently, the topical issue is the use of domestically-produced raw materials in the construction engineering sector. The subject of research are aluminosilicates, calcium and sodium bentonites. Bentonite clays have a high dispersion degree. The main rock-forming mineral of bentonite clays is montmorillonite. A significant proportion of bentonites in the field deposits of the Russian Federation is represented by calcium bentonites. Calcium bentonites have lower sorption characteristics than the sodium ones. To expand the scope of use of alkaline-earth bentonites, various methods of modification are used. Objectives: studying the influence of low-temperature nonequilibrium plasma on the sorption properties of bentonites. Upon the application of plasma-chemical modification, only the surface layer of the material is transformed. The bulk properties of the material are not changed. This is the advantage of plasma chemical technologies. Results: the modifying effect of low-temperature nonequilibrium plasma on the increase of the sorption capacity, strength and desorption properties of bentonites of the Nekrylovsky site of the Tarasovsky field deposit. Conclusions: the high efficiency of a low-temperature nonequilibrium plasma having a complex of physical and chemical effects on the kinetics of sorption and desorption processes with respect to various types of sorbates has been experimentally confirmed.